Internalization of Religious Moderation Through Islamic Religious Education in the Digital Era at the University of Muhammadiyah Gresik - Ahyan Yusuf Sya’bani, Mohammad; Zainuddin, Muhammad; Walid, Muhammad; Haris, Abdul (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This research focuses on the academic condition at the University of Muhammadiyah Gresik which has begun to implement the value of religious moderation. However, these values still need to be internalized more deeply in order to solve problems by referring to the principle of religious moderation. This study uses a qualitative descriptive approach with interview, observation, and documentation data collection techniques. Data analysis was carried out through the stages of collection, reduction, data presentation, and verification of conclusion drawn, with data validity tests using method triangulation techniques, member checks, and long-term utilization. The results of the study show that: 1) The concept of internalization of religious moderation at the University of Muhammadiyah Gresik starts from the seven principles of religious moderation in the Progressive Islamic Treatise which is translated into the Internal Quality Assurance System of Muhammadiyah-Aisyiyah Higher Education (SPMI PTMA). Further implementation is described in the vision, mission, and Semester Learning Plan (RPS) of each course. 2) Lecturers' efforts in implementing religious moderation involve three stages: externalization, objectification, and internalization of national values, tolerance, and pluralism in classroom learning practices. This study provides an overview of the importance of strengthening the internalization of religious moderation in the context of higher education to form the character of students who are tolerant and committed to national values.